Quinoa (Chenopodium quinoa): Nutritional composition and bioactive compounds of grain and leaf, and impact of heat treatment and germination (Scientia Agropecuaria, 2022)
Quinoa (Chenopodium quinoa) is an Andean pseudocereal produced in countries such as Bolivia, Peru, Ecuador and southern Colombia, with more than 3,000 varieties, distinguished by their nutritional properties and adaptation to different agro-ecological zones. Quinoa's nutritional profile stands out for its protein, carbohydrate, lipid and gluten-free content; it is rich in vitamins; and it is an excellent source of minerals, such as calcium, magnesium, iron and phosphorus. It is one of the few foods that have in its composition all the essential amino acids, standing out from other cereals such as rice or wheat. It is an excellent source of bioactive compounds, which have antioxidant, cytotoxic, antidiabetic and anti-inflammatory properties. With respect to quinoa leaves, several studies have indicated that they have higher protein content than grains, as well as inorganic nutrients such as calcium, phosphorus, iron and zinc. In addition, they can potentially serve as a rich source of phenolic compounds and carotenoids. Conventional heat treatments greatly or slightly affect the composition of the food, including bioactive compounds and antioxidant capacity. Germination provides the product with greater bioavailability and an increase in bioactive compounds. The purpose of this work was to document research on quinoa and its leaves, the effect of thermal treatments and germination on its bioactive compounds, in order to promote the creation and innovation of products based on its bioactive compounds, thus combating malnutrition in our population.
Keywords: Quinoa leaves; pseudocereal; amino acids; heat treatments; germination